Brain serotonin synthesis in MDMA (ecstasy) polydrug users: an alpha‐[11C]methyl‐l‐tryptophan study. (21st August 2014) - Booij, Linda; Soucy, Jean‐Paul; Young, Simon N.; Regoli, Martine; Gravel, Paul; Diksic, Mirko; Leyton, Marco; Pihl, Robert O.; Benkelfat, Chawki
Abstract 3, 4‐Methylenedioxymethamphetamine (MDMA, ecstasy) use may have long‐term neurotoxic effects. In this study, positron emission tomography with the tracer alpha‐[11C]methyl‐l‐tryptophan (11C‐AMT) was used to compare human brain serotonin (5‐HT) synthesis capacity in 17 currently drug‐free MDMA polydrug users with that in 18 healthy matched controls. Gender differences and associations between regional 11C‐AMT trapping and characteristics of MDMA use were also examined. MDMA polydrug users exhibited lower normalized 11C‐AMT trapping in pre‐frontal, orbitofrontal, and parietal regions, relative to controls. These differences were more widespread in males than in females. Increased normalized 11C‐AMT trapping in MDMA users was also observed, mainly in the brainstem and in frontal and temporal areas. Normalized 11C‐AMT trapping in the brainstem and pre‐frontal regions correlated positively and negatively, respectively, with greater lifetime accumulated MDMA use, longer durations of MDMA use, and shorter time elapsed since the last MDMA use. Although the possibility of pre‐existing 5‐HT alterations pre‐disposing people to use MDMA cannot be ruled out, regionally decreased 5‐HT synthesis capacity in the forebrain could be interpreted as neurotoxicity of MDMA on distal (frontal) brain regions. On the other hand, increased 5‐HT synthesis capacity in the raphe and adjacent areas could be due to compensatory mechanisms. <boxed-text content-type="graphic" id="jnc12826-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Animal studies showed that MDMA (3, 4‐methylenedioxymethamphetamine, ecstasy) exposure alters brain serotonin neurotransmission. Whether these effects are permanent is unknown. The present human study found that, compared to controls, young adult MDMA users had lower serotonin synthesis in parts of the frontal cortex, and greater serotonin synthesis in other regions, including the brainstem. The strength of these effects correlated with severity of use. The findings may indicate that MDMA can be neurotoxic but the brain may also have the capacity to regenerate, depending on the specific brain region. Longitudinal studies are needed to test the clinical relevance of these findings.